ANALISIS KETIMPANGAN WILAYAH ANTAR KABUPATEN/ KOTA DI PROVINSI SUMATERA SELATAN TAHUN 2011-2015 - Lisa Hermawati; Misnalia Misnalia (KOLEGIAL, 2017)
The purpose of this study is to determine the extent of regional imbalance between regency/city in south Sumatra province. The data used are PDRB data of Regency/City of South Sumatera Province and Regency/City PDRB data at constant value 2010. Analysis tools used in this research are Analysis method of Williamson Index (WI), Gini Index Analysis.The results of this study explain that: (1) Williamson Index analysis of 17 districts/cities in South Sumatra Province results that from 17 districts/cities in South Sumatra Province only 5 districts/cities are very prevalent as it approaches to zero, Lahat Regency, Muara Enim Regency, Musi Rawas Regency, and East Oku District and also 12 other districts/cities are very uneven as it approaches 1. Based on Gini Index analysis from 17 districts/cities in South Sumatera Province, Gini Index calculation results that from 17 regencies/cities in South Sumatera Province there are only 10 regencies/cities in South Sumatera Province Whose numbers range from zero (equal distribution) consist of Ogan Komering Ilir Regency, Banyuasin Regency, South Oku District, Ogan Ilir Regency, Empat Lawang District, Penukal Abab Lematang Ilir Regency, North Musi Rawas Regency, Palembang City, Lubuk Linggau City and City of Prabumulih. While 7 other regencies / cities are worth up to one (perfect inequality) such as Musi Rawas Regency, Muara Enim Regency, Ogan Komering Ulu Regency, East Ogan Komering Ulu Regency, Musi Banyuasin Regency and Pagar Alam City.